Association between polymorphisms of the APOBEC3G gene and chronic hepatitis B viral infection and hepatitis B virus-related hepatocellular carcinoma - He, Xiu-Ting; Xu, Hong-Qin; Wang, Xiao-Mei; He, Xiu-Shu; Niu, Jun-Qi; Gao, Pu-Jun (World journal of gastroenterology : WJG, 2017)
To determine the relationship between five gene single nucleotide polymorphisms and the incidence of hepatitis B virus (HBV) infection and hepatocellular carcinoma (HCC). This association study was designed as a retrospective study, including 657 patients with chronic HBV infection (CHB) and 299 healthy controls. All subjects were ethnic Han Chinese. Chronic HBV-infected patients recruited between 2012 and 2015 at The First Hospital of Jilin University (Changchun) were further classified into HBV-related HCC patients ( = 287) and non-HCC patients ( = 370). Frequency matching by age and sex was performed for each group. Human genomic DNA was extracted from whole blood. Gene polymorphisms were identified using a mass spectroscopic method. There were no significant differences between the genotype and allele frequencies of the rs7291971, rs5757465 and rs5757463 gene polymorphisms, and risk of CHB and HBV-related HCC. The AG genotype and G allele for rs8177832 were significantly related to a decreased risk of CHB (OR = 0.67, 95%CI: 0.47-0.96; OR = 0.69, 95%CI: 0.50-0.95, respectively) and HCC (OR = 0.53, 95%CI: 0.34-0.84; OR = 0.58, 95%CI: 0.39-0.87, respectively). A significant relationship was found between rs2011861 computed tomography, TT genotypes and increased risk of HCC (OR = 1.69, 95%CI: 1.02-2.80; OR = 1.82, 95%CI: 1.08-3.06, respectively). Haplotype analyses showed three protective and four risk haplotypes for HCC. Also, one protective haplotype was found against CHB. This study indicates that the A3G rs8177832 polymorphism is associated with a decreased risk of CHB infection and HCC, while the rs2011861 polymorphism is associated with an increased risk of HCC.